Crop type and altitude are the main drivers of species composition of arable weed vegetation in Tajikistan. (24th June 2015) - Nowak, A; Nowak, S; Nobis, M; Nobis, A; Storkey, Jonathan
Summary The influence of broad‐scale environmental factors on the species composition of segetal weed communities in Tajikistan was investigated. The research was conducted throughout the country, analysing plots of root crops as well as cereals from all phytogeographical regions of Tajikistan, with the exception of the eastern Pamir. The study was based on 440 phytosociological relevées sampled between 2009 and 2013 and analysed using direct and indirect ordinations. A set of environmental variables was obtained for each plot: altitude, mean annual precipitation, mean annual temperature, pH, crop type, longitude, latitude and date of sampling (seasonality). Crop type was the major factor determining species composition, which was related to the different farming practices in roots and cereals. Major changes in weed species composition were also driven by altitude and correlated temperatures. The seasonality of weed communities also had a considerable effect on weed community structure. Samples from spring differed significantly from samples from summer and late summer. Only longitude and soil pH were found to be insignificant. The complete set of environmental variables used in a canonical correspondence analysis explained 8.3% of the species variation in sampled plots. The study showed that despite the very diverse climatic conditions and low intensity of agriculture in Tajikistan, agrocoenoses respond mainly to the type of cultivation practised in arable land.